Effects of Spontaneous Abortion on Women's Psychological Domain of Quality of Life - fadhil, Sarab; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To find out the association between psychological domain of Quality of life with study variable(demographic &reproductive).Methodology: A descriptive Analytical study was conduct on Non-probability (purposive sample)of (200) womenwho have suffering from spontaneous abortion in maternity unit from four hospitals which include Al-Elwyiamaternity teaching hospital, and Baghdad teaching hospital at Al-Russafa sector. Al –karekh maternity hospitaland Al-Yarmook teaching hospital at Al-karekh sector. A questionnaire was used as a tool of data collection for theperiod of February 3rd 2013 to April 26th 2013 and consisted of four parts, including demographic, reproductivecharacteristics, and psychological domain of quality of life. A pilot study was carried out to test the reliability of thequestionnaire and content validity was carried out through the 20 experts. Descriptive statistical analyses wereused to analyze the data.Results :The results of the study revealed that (26.5%) of women their age range (25-29) years, (48%) within thenormal body weight,(27.5%)graduated from primary school, (25%) of their husband graduated from college orinstitute, (80%) housewives, (54.5%) of their husband were employee, (48%) within low category of socioeconomicstatus. And about the reproductive information (66%) of women were primi or multi gravida, and (25%) haveprevious two delivery, and (52.5%) have previous one abortion, also there are association between psychologicaldomain of quality of life and sociodemographic status(Age groups)at (p=0.006), and with reproductive parameters(gravid) at (p=0.031).Recommendations: The study recommended Conduct Structured Teaching Programmed (STP) to pregnantwomen's with history of miscarriage included meaning, causes, and prevention of miscarriage, and Reinforce therole of the psychological care for the women by primary health center. the study recommends to collaborativeaction can Ministry of Health take in distribution of awareness for women towards the problem by conducting abooklet or lectures about miscarriage.